2001
DOI: 10.1152/ajpendo.2001.281.3.e489
|View full text |Cite
|
Sign up to set email alerts
|

Induction of osteoblast differentiation indexes by PTHrP in MG-63 cells involves multiple signaling pathways

Abstract: Parathyroid hormone (PTH)-related peptide (PTHrP) can modulate the proliferation and differentiation of a number of cell types including osteoblasts. PTHrP can activate a G protein-coupled PTH/PTHrP receptor, which can interface with several second-messenger systems. In the current study, we have examined the signaling pathways involved in stimulated type I collagen and alkaline phosphatase expression in the human osteoblast-derived osteosarcoma cells, MG-63. By use of Northern blotting and histochemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 42 publications
5
64
0
Order By: Relevance
“…The MAPK, PKC, PKA and PI3K signaling pathways can all be directly activated downstream of calcium influx [61] . The activation of protein kinase C (PKC) and/or protein kinase A (PKA) plays an essential role in osteoblast differentiation [62] . In our previous study, we have observed activation of the ERK1/2 signaling pathway when osteoblasts were treated with NMDA [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK, PKC, PKA and PI3K signaling pathways can all be directly activated downstream of calcium influx [61] . The activation of protein kinase C (PKC) and/or protein kinase A (PKA) plays an essential role in osteoblast differentiation [62] . In our previous study, we have observed activation of the ERK1/2 signaling pathway when osteoblasts were treated with NMDA [12] .…”
Section: Discussionmentioning
confidence: 99%
“…32 Human OS tumors usually exhibit osteoblast-like features. 3,[33][34][35][36][37][38][39] We demonstrated that differentiation-promoting agents (eg, PPARg agonists and 9-cis retinoic acid) can induce osteoblast differentiation and inhibit OS cell proliferation. 3,40 Here, we investigate whether the disruption of osteoblast differentiation plays a role in OS development.…”
mentioning
confidence: 90%
“…In vitro, PTH inhibits bone marker gene expression and mineralization in differentiated osteoblasts and cementoblasts (49,56). In contrast, PTH rapidly induces osteoblastspecific gene expression in undifferentiated, proliferating osteoblasts (8,16,57,58). Thus, PTH may preferentially stimulate osteoblast differentiation in immature cells while inhibiting it in more mature cells.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
“…A number of signaling transduction pathways have been associated with PTH (8,9,(47)(48)(49)(50). For example, Boguslawski et al (16) showed that PKA and PKC pathways cooperatively interact in PTH-mediated OCN gene expression in rat and human osteoblast cell lines.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
See 1 more Smart Citation